Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.3 - Simplifying Radical Expressions - Exercise Set - Page 433: 75


$2xy^{2} \sqrt[5]( x)^{2}$

Work Step by Step

$\frac{\sqrt[5] 64x^{10}y^{3}}{\sqrt[5] 2x^{3}y^{-7}}$ Using the product and quotient rules for exponents and radicals $= \sqrt[5] \frac{64x^{10}y^{3}}{2x^{3}y^{-7}}$ $= \sqrt[5](32 x^{10-3}. y^{3-(-7)})$ $= \sqrt[5]32 x^{7}. y^{10}$ $= \sqrt[5](2^{5}. x^{7}. y^{10})$ $=(2^{5}. x^{7}. y^{10})^{\frac{1}{5}} $ $=(2^{5}. x^{5}.x^{2}. y^{10})^{\frac{1}{5}} $ $=2xy^{2} \sqrt[5]( x^{2})$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.